La Motivación en el proceso de enseñanza – aprendizaje en los estudiantes de quinto grado de la Unidad Educativa “Mariscal Antonio José de Sucre” del cantón Saquisilí de la provincia de Cotopaxi. - Villacis Oña, Katherine Sulay (2021)
The research report is mainly aimed at the problems that teachers have in the educational process when it comes to checking students' learning achievements. The purpose is to develop guidelines for motivational strategies and techniques for the teaching process. The approach used is mixed because it uses a method to solve the problem and combines qualitative and quantitative aspects for the analysis of motivation. The qualitative method was used in detecting and visualising the problem, as well as in the derivations of interviews, verification and results of written reviews to diagnose the current conditions related to the motivation of teachers to use it in the classroom and the approval of the educational proposal for study, to be verified by experts and users. In the literature review, methods of analysis and synthesis are used in training theories and particularly to establish the strategies and skills of motivation in the educational process. It was feasible because bibliographical information was obtained from different research works and no existing theory was modified. The modelling method was used to shape the system of processes linked to the objectives and to elaborate the proposal. The reason for this approach is that changes should be made through the orientation of technical incentive strategies to optimise the educational process in all subjects.